PERANCANGAN AWAL INTERIOR YAYASAN RUMAH PAGI BAHAGIA DI BINTARO - Adi Ismanto; Michella Angelina; Canisha Chrystella (PROSIDING SERINA, 2021)
Education is the foundation and driving force for the progress of a nation. Indonesia, as a developing country is still looking for a quality education system to produce the best and reliable human resources. Formal education must also be equipped with other supporting education in order to be able to achieve the vision of the country, namely "Educating the Life of the Nation". One of the systems that is also applied in Indonesia is a diverse education system. Indonesia is very rich in linguistic and cultural diversity. Therefore, an education system is created that can adjust to the wealth of the nation. As for the types of levels that can be selected, namely formal, nonformal, and informal. The profile of the PKM Partner "Rumah Pagi Bahagia Foundation" on this activity is a Foundation of Dhuafa Orphans and Environmental Social Institutions. It is a non-profit organization founded on February 26, 2006. Partners have foster children who have a mission one of which is to create education and independence. Currently, Rumah Pagi Foundation uses shophouse building facilities that have not been designed interior to support existing activities and activity programs. Starting from this vision and mission, the PKM team cooperates in the field of interior design that is in accordance with the needs of activities, facilities and is also able to fulfil functions and aesthetics in accordance with the character of Rumah Pagi Indonesia Foundation. So that the activity program can be realized in building facilities and rooms that are functionally and aesthetically appropriate.